2011
DOI: 10.1089/pho.2009.2615
|View full text |Cite
|
Sign up to set email alerts
|

A New Lung Cancer Biomarker—A Preliminary Report

Abstract: In this preliminary report with a limited number of lung cancer patients, we have used SFXS of plasma and sputa as the basis for a new technique identifying elastin as an exclusive lung cancer biomarker. This technique has the potential to become a new protocol for rapid and cost-effective screening and diagnosis of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Figure 2 gives a representation of scatter plot of ratio parameters R 1 (a measure of porphyrin concentration in the erythrocyte, as shown in) 10 11 12 13 14 for the control and smoker sets. It was observed that most of the R 1 values for the smoker group were less than the cutoff value, R 1 = 1 (arbitrarily chosen).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 gives a representation of scatter plot of ratio parameters R 1 (a measure of porphyrin concentration in the erythrocyte, as shown in) 10 11 12 13 14 for the control and smoker sets. It was observed that most of the R 1 values for the smoker group were less than the cutoff value, R 1 = 1 (arbitrarily chosen).…”
Section: Resultsmentioning
confidence: 99%
“…Out of a large number of such bio-molecules such as proteins or amino acids, only a dozen of them fluorescence in the range of 200 to 800 nm. The relative proportion of such fluorescent molecules acts as biomarkers of a certain set of well-defined diseases 9 10 11 12 13 14 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These two signals are fingerprints of biomolecules that are commonly found in tissue or fluid. The nature, quality, and quantity of biomolecules can be correlated to the specific disease of the subjects, as can be shown by the large number of studies on cancer tissues and the blood of inherited disorders [ 7 , 8 , 9 , 10 , 11 , 12 ]. The fluorescent spectral technique can be regarded as a new technique of molecular diagnosis.…”
Section: Introductionmentioning
confidence: 99%